Method for evaluating existence form and measuring relative content of hydrogen in silicon material

By combining DRIFTS and hydrogen content analyzer, the changes in the absorption intensity of the silicon material after annealing at different temperatures were determined, and the problems that are difficult to explore in the presence of hydrogen in silicon material and the annealing and dehydrogenation mechanism are achieved. The precise determination of the existence form and relative content of hydrogen is provided, and the theoretical basis for optimization of the annealing process is provided.

CN119413746AActive Publication Date: 2025-02-11ZHEJIANG UNIV +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411488334.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-11
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The prior art is difficult to fully explore the specific existence form, relative content of hydrogen in silicon materials and the change mechanism of hydrogen removal rate during annealing and dehydrogenation process, resulting in limited process design optimization, making it difficult to effectively alleviate the adverse effects of hydrogen on silicon materials or make full use of it. Its advantageous effect.

Method used

By combining a diffuse reflection Fourier infrared spectrometer (DRIFTS) with a hydrogen content analyzer, the changes in the absorption intensity of Si-Hx bonds after annealing of silicon materials at different temperatures were determined, and the presence and relative content of hydrogen were analyzed.

Benefits of technology

Achieved the accurate determination of the existence and relative content of hydrogen in silicon materials, and a deep understanding of the annealing behavior characteristics and scientific mechanism of hydrogen, providing theoretical basis and practice for the optimization design of dehydrogenation temperature and time during the annealing of silicon materials. guide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119413746A_ABST
    Figure CN119413746A_ABST
Patent Text Reader

Abstract

According to the method for evaluating the existence form and measuring the relative content of hydrogen in the silicon material, diffuse reflection Fourier infrared spectroscopy and a hydrogen content analyzer are combined for implementation, the selected annealing temperature range is 450-1000 DEG C, the difference value between different annealing target temperatures is 150 DEG C or 200 DEG C, the heat preservation time is 0.5, 1, 2, 3 or 6 h, and the heating rate is 10 DEG C / min. The wave number range of diffuse reflection Fourier infrared spectroscopy testing is 500-2500 cm <-1 >, the resolution ratio is 4 cm <-1 >, and 630 cm <-1 >, 900 cm <-1 >, 2000 cm <-1 > and 2100 cm <-1 > are selected as DRIFTS characteristic absorption peaks of SiHx in the silicon material. According to the method, the existence form and the relative content of hydrogen in the silicon material can be roughly measured, and theoretical and practical references are provided for designing annealing and dehydrogenation conditions of the silicon material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen content analysis and testing, and in particular relates to a method for evaluating the existence form of hydrogen in silicon materials and determining the relative content. Background Art

[0002] In the preparation and application of silicon materials, hydrogen, as a key impurity element, exhibits complex and dual influence characteristics. Specifically, in the granular polycrystalline silicon material prepared by silane fluidized bed technology, the hydrogen content is relatively high. These hydrogen elements will be released rapidly during the melting stage of the silicon material, causing the so-called "hydrogen jump" phenomenon, resulting in sputtering of the silicon melt, thereby destroying the stability of the crystal growth process and reducing the service life of the thermal field. On the other hand, in the manufacturing process of silicon-based solar cells, hydrogen elements can be introduced into silicon materials through plasma-assisted hydrogen-rich film deposition or hydrogen ion implantation, effectively passivating the dangling bonds on the surface of the solar cell, thereby significantly improving the minority carrier lifetime and having a positive impact on the battery performance.

[0003] Previous studies have shown that hydrogen in silicon materials will escape from the material during the annealing process, and the efficiency of the escape process is significantly affected by the annealing temperature and time. However, to date, the specific existence form and relative content of hydrogen in granular silicon, as well as the fundamental mechanism of how the hydrogen removal rate changes with temperature and time during annealing and dehydrogenation, have not been fully and deeply explored. This lack of scientific knowledge has greatly hindered the further optimization of process design, making it difficult to effectively alleviate the adverse effects of hydrogen in silicon materials, and its beneficial effects are also difficult to fully amplify. Therefore, in-depth exploration of the existence form of hydrogen in granular silicon and its annealing and dehydrogenation mechanism is of vital scientific significance and application value for improving the growth quality of CZ silicon crystals and optimizing the hydrogen passivation process of solar cells.

[0004] Diffuse reflectance Fourier infrared spectrometer is an advanced infrared spectroscopy analysis device that works in reflection mode. It can accurately convert the light signal reflected by the sample into an infrared spectrum, thereby revealing key information such as the molecular structure and chemical bonds of the sample. The instrument is known for its non-destructive testing capabilities and high-precision measurement performance. It is particularly suitable for direct and accurate measurement of solid powders and complex multi-component samples; the hydrogen content analyzer uses high-temperature melting technology to ensure that various forms of hydrogen elements in the sample can be completely released and converted into hydrogen. By accurately measuring the change in thermal conductivity, the total hydrogen content in the sample can be accurately determined. Based on these two methods, the present invention is proposed to address the above technical problems. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention aims to provide a method for evaluating the existence form of hydrogen in silicon materials and determining the relative content thereof. The method determines the hydrogen content and diffuse reflectance Fourier infrared spectroscopy test of the silicon materials after annealing at different temperatures, and compares the change of hydrogen content with the Si-H in the Fourier diffuse reflectance infrared spectroscopy. x The change of bond absorption strength is analyzed, and the removal temperature and relative content of different forms of hydrogen in silicon materials are analyzed. This is achieved through the following technical solutions:

[0006] A method for evaluating the existence form of hydrogen in silicon material and determining the relative content thereof, comprising the steps of:

[0007] Step 1: Take a sample of the original silicon material and measure the hydrogen content using a hydrogen content analyzer. The test is performed twice, and the hydrogen content is recorded and the average value is taken, which is recorded as [H]. 0 .

[0008] Step 2: Take the original silicon material sample, crush it with a mortar and grind it into 0.15-0.25mm chips, and perform DRIFTS test under vacuum; the test wave number range is 2500-500cm -1 , resolution 4cm -1 .

[0009] Step 3: Take another batch of original silicon material samples, divide them into multiple groups, heat them to different target annealing temperatures at a heating rate of 10℃ / min and keep them at different temperatures for different times, and then cool them down with the furnace. The annealing temperature range is 450-1000℃, the difference between different annealing target temperatures is 150℃ or 200℃, and the holding time is 0.5, 1, 2, 3 or 6h.

[0010] Step 4: Divide each group of annealed silicon material samples in step 3 into two parts, one of which is subjected to hydrogen content test, and the test steps are the same as step 1; the other is subjected to DRIFTS test, and the test steps and parameters are the same as step 2.

[0011] Step 5: Draw a curve of hydrogen content versus annealing temperature and time based on the average value of hydrogen content of each group of samples measured in step 4.

[0012] Step 6: Based on the data obtained in step 4, draw the DRIFTS stacking diagram of silicon materials annealed at the same annealing temperature for different times and the DRIFTS stacking diagram of silicon materials annealed at different temperatures for the same annealing time; compare the SiH x The intensity of the characteristic peak changes, the characteristic peak is located at 630cm -1 、900cm -1 , 2000cm -1 and 2100cm -1 about.

[0013] Step 7: Compare the temperature and time at which the hydrogen content in the curve described in step 5 changes significantly with the temperature and time at which the SiHx absorption intensity in the diffuse reflectance Fourier transform infrared spectrum described in step 6 changes significantly, and analyze the existence state of hydrogen in the silicon material;

[0014] Step 8: Based on the amount of hydrogen removed and the initial content [H] 0 The ratio of this form of hydrogen to all forms of hydrogen is calculated by the ratio of , and the percentage of each form of hydrogen is calculated according to the following formula:

[0015] H 1p =[H] 1 / [H] 0 ×100%

[0016] In the formula, H 1p H 1 The percentage of hydrogen in this form to all forms of hydrogen, [H] 1 H 1 The content of hydrogen in the form of 1 When referring to the amount of hydrogen removed at a certain stage, [H] 1p represents the dehydrogenation rate.

[0017] The method of the present invention combines DRIFTS technology with a hydrogen content analyzer to accurately determine the existence form and relative content of hydrogen in silicon materials. Specifically, the method uses DRIFTS testing and hydrogen content analysis technology to systematically measure the relative content of SiH in silicon materials for raw and annealed silicon material samples. x The absorption intensity of the relevant characteristic peaks and the hydrogen content. Furthermore, the present invention deeply analyzes the correlation between these measurement results and the annealing temperature and time, so as to clearly reveal the specific existence form and relative proportion of hydrogen in the silicon material.

[0018] The implementation of this method not only helps to deeply understand the annealing behavior characteristics of hydrogen in silicon materials, but also provides valuable insights into the scientific mechanism behind it. Therefore, the present invention provides a solid theoretical basis and practical guidance for the optimization design of dehydrogenation temperature and time during the annealing process of silicon materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 DRIFTS spectrum of the native silicon material sample in the embodiment, in which the wave value of each absorption peak and its attribution are marked;

[0020] Figure 2 is a curve showing the change of hydrogen content of silicon material samples annealed at different temperatures as a function of annealing time in the embodiment;

[0021] Figure 3 DRIFTS diagram of silicon materials annealed at different temperatures and for different times in the embodiments. DETAILED DESCRIPTION

[0022] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments to provide a better understanding of the present technical solution.

[0023] The present invention provides a method for evaluating the existence form of hydrogen in silicon material and determining the relative content thereof, comprising the following steps:

[0024] S1: Hydrogen content test of raw silicon material sample: Take 0.5g raw silicon material sample and place it in a graphite crucible. After rapid melting in a hydrogen content analyzer, the hydrogen content value is obtained. The test is performed twice and the average value is calculated.

[0025] S2: DRIFTS test of original samples: 1g of original silicon material sample was taken and ground into fragments of about 0.2mm in a quartz mortar to expose the internal structure of the silicon material as much as possible. The fragments were subjected to DRIFTS test. The wave number range of the test was 2500-500cm -1 , resolution 4cm -1 .

[0026] S3: Silicon material annealing: Weigh 18g of silicon material and place it in a corundum boat. Start from room temperature and heat it to different target annealing temperatures at a heating rate of 10℃ / min in an argon atmosphere. Keep it for different times and then cool it with the furnace. The annealing temperature range is 450-1000℃, the difference between different annealing target temperatures is 150℃ or 200℃, and the holding time is 0.5, 1, 2, 3 or 6 hours.

[0027] S4: Testing hydrogen content of annealed silicon material: Testing and recording hydrogen content of the annealed silicon material according to the steps described in S1.

[0028] S5: DRIFTS test of annealed silicon material: Perform DRIFTS test on the annealed silicon material according to the steps described in S2.

[0029] S6: Plotting and analysis: Plot the variation curve of hydrogen content in silicon materials after annealing at different temperatures with annealing holding time and the DRIFTS spectrum of silicon material samples annealed at different temperatures and for different times, and analyze the hydrogen content and SiH in the DRIFTS spectrum. x The relationship between the absorption intensity of the relevant peak and the annealing temperature and time can be used to determine the existence form of hydrogen in the silicon material.

[0030] S7: Calculate the relative content of a certain form of hydrogen: Calculate the percentage of each form of hydrogen according to the following formula:

[0031] H 1p =[H] 1 / [H] 0 ×100%

[0032] In the formula, H 1p H 1 The percentage of hydrogen in this form to all forms of hydrogen, [H] 1 H 1 The content of hydrogen in the form of 1 When referring to the amount of hydrogen removed at a certain stage, [H] 1p represents the dehydrogenation rate.

[0033] Example

[0034] A method for determining the existence form and relative content of hydrogen in silicon material using diffuse reflectance Fourier infrared spectroscopy and a hydrogen content analyzer, the specific implementation process is as follows:

[0035] 1) Take 0.5 grams of the original granular polysilicon material sample and use the hydrogen content analyzer to measure the hydrogen content twice to ensure the accuracy of the instrument. The first measurement result shows that the hydrogen content is 21.6ppmw (parts per million by weight), and the second measurement result is 22.5ppmw. The calculated average value is 22.1ppmw.

[0036] 2) Take another 1 gram sample of the original granular polysilicon material, crush it in a quartz grinder and refine it into fragments of about 0.2 mm. Then, use a diffuse reflectance Fourier transform infrared spectrometer (DRIFTS) to measure the infrared spectrum of the fragments. The results are shown in the attached figure. Figure 1 .

[0037] 3) Design and execute 16 sets of annealing experiments, each set of experiments uses 18 grams of original granular polysilicon material samples from the same batch. The samples are placed in a corundum porcelain boat, eight of which are heated from room temperature to 450 or 650°C at a heating rate of 10°C / min in an argon atmosphere, and kept warm for 1, 2, 3, and 6 hours, respectively, and then cooled with the furnace. The other eight sets are heated from room temperature to 800 or 1000°C at a heating rate of 10°C / min in an argon atmosphere, and kept warm for 0.5, 1, 2, and 3 hours, respectively, and then cooled with the furnace.

[0038] 4) Repeat the hydrogen content test in step 1) and the DRIFTS spectrum determination in step 2) for all annealed samples to ensure that the test conditions are consistent with the original samples. The hydrogen content data in the test results are summarized in Table 1.

[0039] Table 1

[0040]

[0041] 5) Calculate the dehydrogenation rate according to the above formula based on the test data, and draw a curve chart of the hydrogen content and dehydrogenation rate in the granular polysilicon material as a function of annealing temperature and time. Figure 2 .

[0042] 6) Summarize and analyze the DRIFTS spectra of all samples, and draw a comprehensive spectrum to show the infrared spectral characteristics of granular polysilicon materials under different annealing conditions. The results are shown in the attached figure. Figure 3 The first row of data shows the effect of temperature when the annealing time is the same, and the second row of data shows the effect of annealing time at the same annealing temperature.

[0043] 7) Combine the hydrogen content test data and curves with the SiH x The change of absorption peak intensity analyzes the existence form of hydrogen in the particles. At 450-800℃, the hydrogen content in granular polysilicon material shows a gradual downward trend. After annealing at 650℃ for 6 hours, the dehydrogenation rate reaches 45%. However, in this temperature range, the SiH x The intensity of the absorption peak did not decrease significantly, indicating that the main removal in this temperature range was hydrogen that was not infrared active, such as hydrogen molecules (H 2 ) or hydrogen atoms (H). This type of hydrogen is relatively easy to remove due to its poor thermal stability. When the annealing temperature is increased to 1000℃, the hydrogen content in the granular polysilicon material can be sharply reduced after annealing for only 0.5h, and the dehydrogenation rate is as high as 51%. However, even for the granular polysilicon material annealed at 1000℃ for 1 hour, the SiH x The intensity of the absorption peak decreased slightly compared with the sample annealed at 800°C for 1 hour. This result shows that in the early stage of annealing at 1000°C, the main hydrogen removed is still hydrogen molecules or hydrogen atoms that are not infrared active. In addition, the dehydrogenation rate of annealing at 1000°C for 0.5 hours is similar to that of annealing at 650°C for 6 hours, which further confirms that this type of hydrogen accounts for between 45% and 51% of the total hydrogen content, and its thermal stability at high temperatures is greatly reduced, making it extremely easy to remove. However, when the treatment time at 1000°C exceeds 0.5 hours, the dehydrogenation rate decreases significantly. At the same time, the SiH x The intensity of the absorption peak decreased significantly. This change indicates that the SiH x This part of hydrogen has higher thermal stability and is more difficult to remove, accounting for about 50% of the total hydrogen content.

Claims

1. A method for evaluating the existence form and relative content of hydrogen in silicon material, characterized in that The method is carried out by combining diffuse reflectance Fourier infrared spectroscopy with a hydrogen content analyzer, and specifically includes the following steps: 1) Take a sample of the original silicon material and measure the hydrogen content using a hydrogen content analyzer. The test is performed twice, and the hydrogen content is recorded and the average value is taken, which is recorded as [H]0; 2) Take the original silicon material sample, crush and grind it into crumbs with a mortar, and perform DRIFTS test under vacuum; 3) Taking another batch of original silicon material samples, dividing them into multiple groups, heating them to different target annealing temperatures at a heating rate of 10°C / min and keeping them at different temperatures for different times, and then cooling them in the furnace; 4) Each group of annealed silicon material samples in step 3) is divided into two parts, one of which is subjected to hydrogen content test, and the test steps are the same as step 1); the other is subjected to DRIFTS test, and the test steps and parameters are the same as step 2); 5) plotting a curve of hydrogen content versus annealing temperature and time based on the average value of hydrogen content of each group of samples measured in step 4); 6) based on the data obtained in step 4), a DRIFTS stacking diagram of silicon materials annealed at the same annealing temperature for different times and a DRIFTS stacking diagram of silicon materials annealed at different temperatures for the same annealing time are drawn; 7) Compare the temperature and time at which the hydrogen content in the curve of step 5) changes significantly with the SiH in the diffuse reflectance Fourier transform infrared spectrum of step 6). x The temperature and time at which the absorption intensity changes significantly are used to analyze the existence state of hydrogen in the silicon material; 8) According to the ratio of the amount of hydrogen removed in a certain form to the initial content [H]0, the proportion of hydrogen in this form to all forms of hydrogen is calculated, and the percentage content of each form of hydrogen is calculated according to the following formula: H 1p =[H]1 / [H]0×100% In the formula, H 1p is the percentage of hydrogen in the form of H1 to all forms of hydrogen, [H]1 is the content of hydrogen in the form of H1; when [H]1 in this formula refers to the content of part of the hydrogen removed at a certain stage, [H] 1p represents the dehydrogenation rate.

2. A method for evaluating the existence form and determining the relative content of hydrogen in silicon material as claimed in claim 1, characterized in that In step 2), the particle size of the debris is 0.15-0.25 mm.

3. A method for evaluating the existence form and determining the relative content of hydrogen in silicon material as claimed in claim 1, characterized in that The wave number range of DRIFTS test is 2500-500cm -1 , resolution 4cm -1 .

4. A method for evaluating the existence form and determining the relative content of hydrogen in silicon material as claimed in claim 1, characterized in that The annealing temperature range is 450-1000°C, the difference between different annealing target temperatures is 150°C or 200°C, and the holding time is 0.5, 1, 2, 3 or 6h.

5. A method for evaluating the existence form and determining the relative content of hydrogen in silicon material as claimed in claim 1, characterized in that Select 630cm -1 、900cm -1 , 2000cm -1 and 2100cm -1 As SiH x DRIFTS characteristic absorption peak.

Citation Information

Patent Citations

  • Analysis method for silicon hydrogen content in hydrogen-containing silicone oil

    CN103674889A

  • Pretreatment technology for improving quality of polycrystalline silicon film

    CN103820767A

  • Quantitative analysis method of hydrogen in porous silica

    CN110892248A

  • Semiconductor device and manufacture thereof

    JP1987055965A

  • Estimation method of decrease amount of defect concentration of amorphous silicon after hydrogenation annealing

    JP1996078429A